GLOBAL SILICATE WEATHERING AND CO2 CONSUMPTION RATES DEDUCED FROM THE CHEMISTRY OF LARGE RIVERS - Gaillardet J.; Louvat P.; Allègre C.J.; Dupré B. (My University, 1999)
The main problem associated with the study of silicate weathering using river dissolved load is that the main control of solute chemistry is lithology and that all rivers are influenced by carbonate and evaporite weathering. In this paper, newly compiled data on the 60 largest rivers of the world are used to calculate the contribution of main lithologies, rain and atmosphere to river dissolved loads. Technically, an inverse method is used to solve a model containing of a series of mass budget equations relating river concentrations to chemical weathering products and atmospheric inputs. New estimates of global silicate weathering fluxes and associated CO2 consumption fluxes are given. The role of basalt weathering on oceanic islands and volcanic arcs is emphasized. For each large river, an attempt is made to calculate chemical weathering rates of silicates per unit area. Only relative chemical weathering rates can be calculated. The relationships between the chemical weathering rates of silicates and the possible controlling parameters are explored. A combined effect of runoff-temperature and physical denudation seems to explain the variability of modern silicate chemical weathering rates. The results of this study highlight the coupling between the physical and the chemical processes of silicate weathering. Only an active physical denudation of continental rocks seems to be able to maintain high chemical weathering rates and significant CO2 consumption rates.